MAKNA KONTEKSTUAL BUDAYA PADA LAGU KOMANG KARYA RAIM LAODE DAN LAGU MARRY YOU KARYA BRUNO MARS (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the cultural contextual meanings in the lyrics of Raim Laode's song Komang and Bruno Mars' song Marry You. This study employed a descriptive qualitative approach with text analysis methods. The data consisted of song lyrics, analyzed based on their underlying social and cultural contexts. The analysis employed contextual semantics, semiotics, and hermeneutics to understand the denotative and connotative meanings of the lyrics. The results show that Komang's song represents Indonesian cultural values ​​that emphasize loyalty, sincerity, sacrifice, and emotional depth through the use of metaphorical and symbolic language. Meanwhile, Marry You reflects Western culture, which emphasizes individual freedom, spontaneity, and directness in expressing love through straightforward language. These differences indicate that the meanings of song lyrics are strongly influenced by the composer's cultural background. Thus, song lyrics serve not only as a medium for emotional expression but also as a reflection of cultural identity and societal perspectives on love and relationships.